Antithrombotic triple therapy and coagulation activation at the site of thrombus formation: a randomized trial in healthy subjects. (16th October 2014) - Weisshaar, S.; Litschauer, B.; Gouya, G.; Mayer, P.; Smerda, L.; Kapiotis, S.; Kyrle, P. A.; Eichinger, S.; Wolzt, M.
Summary Background Patients with acute coronary syndrome and concomitant atrial fibrillation may require antithrombotic triple therapy but clinical evidence of safety and efficacy is poor. We have therefore studied the combination of different antithrombotic medicines for coagulation activation in an in vivo model in the skin microvasculature. Methods and Results Platelet activation (β‐thromboglobulin [β‐TG]) and thrombin generation (prothrombin fragment 1 + 2 [F1+2], thrombin‐antithrombin complex [TAT]) were studied in an open‐label, randomized, parallel group trial in 60 healthy male subjects (n = 20 per group) who received ticagrelor and acetylsalicylic acid (ASA) in combination with dabigatran (150 mg bid), rivaroxaban (20 mg od) or phenprocoumon (INR 2.0–3.0). Coagulation biomarkers in shed blood were assessed at 3 h after monotherapy with the medicines under study, at 3 h after triple therapy dosing and at steady state trough conditions. Single doses of ticagrelor, dabigatran or rivaroxaban caused comparable decreases in shed blood β‐TG and were more pronounced than phenprocoumon at an INR of 2.0–3.0. In contrast, thrombin generation was more affected by rivaroxaban and phenprocoumon than by dabigatran. During triple therapy a similarly sustained inhibition of platelet activation and thrombin generation with a maximum decrease of β‐TG, F1+2 and TAT at 3 h post‐dosing was noted, which remained below pre‐dose levels at trough steady state. Conclusion A triple therapy at steady state with ticagrelor plus ASA in combination with dabigatran or rivaroxaban is as effective as a combination with phenprocoumon for platelet activation and thrombin generation in vivo.